Lymphocyte levels in Crohn’s disease patients in clinical remission are significantly lower than those in healthy people - Asi He; Tulan Hu; Linzhen Li (European Journal of Medical Research)
Abstract Background and purpose Inflammatory bowel disease (IBD) is a chronic, non-specific inflammatory bowel disease caused by multiple causes. Lymphocytes migration is involved in the pathogenesis of IBD. The purpose of this study was to evaluate whether there were differences in blood lymphocytes levels between IBD patients in clinical remission and healthy people. Patients and methods A total of 94 Crohn’s disease (CD) and 20 ulcerative colitis (UC) patients were included in this study. Ninety-four people who underwent physical examination in our hospital were randomly selected as controls. We analyzed whether there were differences in white blood cell count, neutrophil count, neutrophil percentage, lymphocyte count, lymphocyte percentage between CD patients, UC patients, and healthy people. Results There were significant differences in lymphocyte count (P < 0.001), lymphocyte percentage (P < 0.001), neutrophil count (P = 0.038), and neutrophil percentage (P < 0.001) between CD patients and normal people, but no statistically significant differences in sex (P = 0.216), age (P = 0.745), and white blood cell count (P = 0.757). UC patients had significant differences in white blood cell count (P = 0.005), lymphocyte count (P = 0.010), and neutrophil count (P = 0.023), but no difference in lymphocyte percentage (P = 0.968) and neutrophil percentage (P = 0.461). Conclusions The white blood cell count of CD patients was not significantly different from that of normal people, but the lymphocyte count and lymphocyte percentage were significantly different from that of healthy people. Similar results were not found in UC patients.